2018
DOI: 10.1002/dev.21610
|View full text |Cite
|
Sign up to set email alerts
|

Auditory structural connectivity in preterm and healthy term infants during the first postnatal year

Abstract: Assessing language development in the first postnatal year is difficult, as receptive and expressive skills are rudimentary. Although outward manifestations of change are limited, the auditory language system is thought to undergo critical development at this age, as the foundations are laid for the rapid onset of spoken language in the second and third years. We recruited 11 infants, 7 healthy controls (gestational age = 40.69 ± 0.56; range from 40 to 41.43) and preterm babies (gestational age = 28.04 ± 0.95;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…In addition to confirming previous findings regarding the similarity of the FFR between newborns and adults in terms of neural encoding of the voice pitch, results revealed that the ability of the newborn brain to encode spectrotemporal fine structure is weaker than that of adults, especially for higher sound frequencies. 48 In line with the previous literature, their results suggest that the neural encoding of the temporal fine structure is not yet fully mature at birth, but would require sound, language exposure, and time 47 57 58 to further develop to the level of maturity observed in adults. Overall, newborn studies demonstrate that the FFR is a brain response whose maturity would be affected by not only the maturation of brain tissues but also by the existence of certain postnatal stimulation received by the infant.…”
Section: The Neonatal Frequency-following Response In Clinical Popula...supporting
confidence: 85%
See 2 more Smart Citations
“…In addition to confirming previous findings regarding the similarity of the FFR between newborns and adults in terms of neural encoding of the voice pitch, results revealed that the ability of the newborn brain to encode spectrotemporal fine structure is weaker than that of adults, especially for higher sound frequencies. 48 In line with the previous literature, their results suggest that the neural encoding of the temporal fine structure is not yet fully mature at birth, but would require sound, language exposure, and time 47 57 58 to further develop to the level of maturity observed in adults. Overall, newborn studies demonstrate that the FFR is a brain response whose maturity would be affected by not only the maturation of brain tissues but also by the existence of certain postnatal stimulation received by the infant.…”
Section: The Neonatal Frequency-following Response In Clinical Popula...supporting
confidence: 85%
“…In this sense, it is important to highlight that after birth, the newborn's auditory system is still immature and is not yet able to encode high spectral components of speech. 46 47 Therefore, the typical stimuli commonly used for the study of the neural encoding of the characteristics of speech sounds in adults, when used in newborns, only permit the optimal study of neural encoding of the fundamental frequency of the stimulus and its low-frequency harmonics. This provides a measure to study whether the newborn brain is capable of encoding inflections in the pitch contour of the voice, which are one of the main speech features in tonal languages such as Mandarin.…”
Section: Technical Aspects For Obtaining a Neonatal Ffr: Stimulation ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although caution is advised when translating and interpreting adult signatures in the immature brain 37 , there is considerable evidence to support the validity of this approach. Core structural features of the mature adult brain are developed in term-aged infants 38,39 . We see functional responses 4043 , connectivity patterns, and resting state activity 44,45 exhibit similar features to adult brain activity.…”
Section: Discussionmentioning
confidence: 99%
“…However, as suggested by work on movement and music in infants, the perception of musical rhythm in infancy likely involves interactions between developing auditory, motor, and vestibular systems (Gerry et al, 2010; Phillips‐Silver & Trainor, 2005)—systems that we hypothesize are initially weakly and diffusely coupled in infancy (Sheya & Smith, 2010). Already, many white‐matter tracts in the auditory system have developed by early infancy (Zubiaurre‐Elorza et al, 2018), possibly indicating that developing auditory, motor, and vestibular systems are structurally linked in early infancy. To account for auditory–vestibular interactions, we expand Tichko and Large (2019)’s model, a multi‐frequency network of non‐linear oscillators with Hebbian plasticity, to include an additional motor network, allowing the model to receive vestibular inputs, such as infant bouncing.…”
Section: Methodsmentioning
confidence: 99%